Debatable Aspects of the Concept of Tax Expenditures: Taxes - Sokolovska , Alla; Zatonatska, Tetiana (Ekonomika, 2022)
Despite the implementation of the concept of tax expenditures in the budgetary practice of many countries, theoretical studies of tax expenditures as a basis for their identification and quantification are still relevant. The emergence and development of the concept is accompanied by heated discussions about definition of normativе (benchmark) structure of tax and tax expenditures, as well as the classification of their individual elements. As a result, there is no uniform approach to defining the conceptual model of benchmark structure. This complicates the introduction of the concept of tax expenditures in those countries that set such a task for themselves, as well as their comparative qualitative and quantitative analysis in different countries. The purpose of this article is to generalize and further develop scientific approaches to determining the benchmark structure of the tax and its individual elements, as well as tax benefits and tax expenditures. The main results of this study are the classification of the main elements of the basic structure of the tax into groups and justification of their role in the identification of tax expenditures; defining “structural benefits” and “basic tax structure”; analysis of the report on other tax benefits in Ukraine and determination of the place and role of “structural benefits” in it.
Keywords: Tax benefits; Normativе structure of the tax; Benchmark structure; Tax expenditures; Structural benefits